Study of the relationship between the effective teaching behaviour of physical education teachers and students` learning efficiency - Shih, C.Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this research was to investigate the current state of college/university physical education teachers` effective teaching behaviors, and their students learning efficiency in physical education classes. In addition, the effect of teacher and student backgrounds was also considered in relation to learning efficiency. Methods Questionnaires were used to collect the data needed for this research. The content of the questionnaires included: personal information, measurement of effective teaching behaviors including five sections (preparation before teaching, systematic way of presenting teaching materials, teaching strategy, teaching evaluation and communication between teachers and students) and measurement of students` learning efficiency, which included three sections (cognition, situation and technique). Physical education teachers at universities in Chiayi and Tainan area and students studying at these universities were selected as subjects for this study. Questionnaires were returned from 103 teachers and from 853 students. Descriptive statistics, independent sample t-test, one-way ANOVA, Pearson correlation, canonical correlation and multiple regression analysis was used to analyse the data. Results The findings from this study indicated that: 1. University physical education teachers received high ratings on total effective teaching behaviours; 2. University students received medium-high ratings on learning efficiency at physical education classes; 3. Significant gender differences were shown among teachers with respect to current teaching status and effective teaching behaviours. 4. Significant differences were showed among students with respect to gender, age, school and, physical education grades, levels of competition and learning efficiency; 5. A positive correlation was shown between effective teaching behaviours and students` learning efficiency; and 6. The preparation before teaching, teaching evaluation, teaching strategy and communication between teachers and students in effective teaching behaviours can provide an effective prediction and explanation for the students` learning efficiency. Effective teaching behaviours were defined as part of the teaching process and individual behaviour was exhibited for the purpose of achieving the educational goals which may have an impact on students` learning efficiency.